Enhanced structure and function of human pluripotent stem cell‐derived beta‐cells cultured on extracellular matrix. (4th November 2020) - Singh, Reena; Cottle, Louise; Loudovaris, Thomas; Xiao, Di; Yang, Pengyi; Thomas, Helen E.; Kebede, Melkam A.; Thorn, Peter
Abstract: The differentiation of human stem cells into insulin secreting beta‐like cells holds great promise to treat diabetes. Current protocols drive stem cells through stages of directed differentiation and maturation and produce cells that secrete insulin in response to glucose. Further refinements are now needed to faithfully phenocopy the responses of normal beta cells. A critical factor in normal beta cell behavior is the islet microenvironment which plays a central role in beta cell survival, proliferation, gene expression and secretion. One important influence on native cell responses is the capillary basement membrane. In adult islets, each beta cell makes a point of contact with basement membrane protein secreted by vascular endothelial cells resulting in structural and functional polarization. Interaction with basement membrane proteins triggers local activation of focal adhesions, cell orientation, and targeting of insulin secretion. This study aims to identifying the role of basement membrane proteins on the structure and function of human embryonic stem cell and induced pluripotent stem cell‐derived beta cells. Here, we show that differentiated human stem cells‐derived spheroids do contain basement membrane proteins as a diffuse web‐like structure. However, the beta‐like cells within the spheroid do not polarize in response to this basement membrane. We demonstrate that 2D culture of the differentiated beta cells on to basement membrane proteins enforces cell polarity and favorably alters glucose dependent insulin secretion. Abstract : Glucose stimulated insulin secretion is compromised in stem cell‐derived beta cells. In native islets, beta cell microenvironment play critical role in glucose sensing and stimulated insulin secretion. Reconstructing beta cell niche in vitro by introducing basement membrane proteins in planar culture, decreases basal insulin secretion, and enhances stimulation index in human pluripotent stem cell‐derived beta cells.